Manajemen Program Pembinaan Akhlak dalam Upaya Membentuk Akhlakul Karimah Peserta Didik di MTs Al Ittihadiyah Mamiyai - Harahap, Nadya Arifah Malasri; Rohman, Fatkhur (Universitas Negeri Malang, 2024)
Abstract: This study aims to determine the evaluation system of student moral development programs at MTs Al Ittihadiyah Mamiyai. The focus of the study in this study is three things, namely the planning of student moral development programs, the form of implementing student moral development programs, and the form of evaluating student moral development programs at MTs Al Ittihadiyah Mamiyai. The method used in this study is a qualitative method with a descriptive approach. The data collection techniques used in this study were observation, interviews, and documentation. The results of this study show that: (1) The planning of the student moral development program is prepared jointly with all teacher councils and administration in a meeting. The preparation of this program plan is made so that moral development activities can run regularly and purposefully. In the preparation of the moral development program, several things are determined, including, plans for making activity proposals, funding, goal determination, setting the time and schedule for implementation, availability of infrastructure facilities and coaching materials; (2) Implementation of moral formation programs, namely reading juz amma every morning, praying dhuha, cult, reading yasin every Friday, muhadharah and tahfidz activities carried out every Saturday; (3) The evaluation is carried out in the form of monthly meetings three times containing reports on the extent of the coaching they have done with the principal as controlling. With the moral development program implemented at MTs, changes began to be seen from students, who were usually less polite to more polite, who usually lacked confidence in appearing in front of many people after participating in the moral coaching program to be more confident, who usually did not understand what was good and bad now understand and can distinguish between good and bad.Keywords: Evaluation System, Moral Development Abstrak: Penelitian ini bertujuan untuk mengetahui sistem evaluasi program pembinaan akhlak siswa di MTs Al Ittihadiyah Mamiyai. Fokus kajian dalam penelitian ini ada tiga hal yakni perencanaan program pembinaan akhlak siswa, bentuk pelaksanaan program pembinaan akhlak siswa, dan bentuk evaluasi program pembinaan akhlak siswa di MTs Al Ittihadiyah Mamiyai. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan pendekatan deskriptif. Adapun Teknik pengumpulan data yang digunakan dalam penelitian ini adalah observasi, wawancara, dan dokumentasi. Hasil penelitian ini menunjukkan bahwa : (1) Perencanaan program pembinaan akhlak peserta didik disusun secara bersama-sama dengan seluruh dewan guru dan tata usaha dalam sebuah rapat. Penyusunan rencana program ini dibuat agar kegiatan pembinaan akhlak dapat berjalan teratur dan terarah. Dalam penyusunan program pembinaan akhlak ditentukan beberapa hal antara lain, rencana pembuatan proposal kegiatan, pendanaan, penentuan tujuan, penetapan waktu dan jadwal pelaksanaan, ketersediaan sarana prasarana serta materi pembinaan; (2) Pelaksanaan program pembinaan akhlak yaitu membaca juz amma setiap pagi, sholat dhuha, kultum, membaca yasin setiap hari jumat, kegiatan muhadharah dan tahfidz yang dilaksanakan setiap hari sabtu; (3) evaluasi yang dilakukan berbentuk rapat bulanan sebanyak tiga kali berisi laporan tentang sejauh mana pembinaan yang mereka lakukan dengan kepala sekolah sebagai controlling. Dengan adanya program pembinaan akhlak yang dilaksanakan di MTs mulai terlihat perubahan dari para peserta didik, yang biasanya kurang sopan menjadi lebih sopan, yang biasanya kurang percaya diri tampil didepan banyak orang setelah mengikuti program pembinaan akhlak menjadi lebih percaya diri, yang biasanya belum paham mana yang baik dan buruk sekarang sudah paham dan bisa membedakan mana yang baik dan yang buruk.Kata kunci: Sistem Evaluasi, Pembinaan Akhlak